Incorporating deep features extracted from convolutional neural networks to utilize machine learning classifiers for improved identification of Maize Leaf Disease - Khan, Shama; Arafat, Mohammad; Dein, Mosleh Al; Niloy, Md. Tifur Waesh; Mahmud, Mufrad (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.